Aprimoramento e reforma de uma lavadoura de louças industrial - Zimmermann, Fabio Jose (2014)
The work is the improvement and renovation of an industrial dishwasher a washing. The washer consists of two pumps that are responsible for washing and rinsing the dishes, for resistance to heat water for sensors and operation buttons. Besides the reform, the work shows the design and implementation of electrical wiring for each motor, resistors and buttons of both the power, and the part of signals, and also the use of the Arduino system to automate the machine and its program written in C language.